2021
DOI: 10.5194/soil-7-693-2021
|View full text |Cite
|
Sign up to set email alerts
|

The central African soil spectral library: a new soil infrared repository and a geographical prediction analysis

Abstract: Abstract. Information on soil properties is crucial for soil preservation, the improvement of food security, and the provision of ecosystem services. In particular, for the African continent, spatially explicit information on soils and their ability to sustain these services is still scarce. To address data gaps, infrared spectroscopy has achieved great success as a cost-effective solution to quantify soil properties in recent decades. Here, we present a mid-infrared soil spectral library (SSL) for central Afr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…Works such as from [10], the European LUCAS dataset modeled by [62,63], as well as the U.S. soil spectral data modeled by [23,64,65], were important to show the community the importance and potential of the technique. A free repository such as by [66] have great importance to make this grow since users have access to data. Therefore, our initiative demonstrates the importance of providing online results to end-users and this may encourage other working groups to improve similar new systems.…”
Section: The Web Service Advantages and Limitationsmentioning
confidence: 99%
“…Works such as from [10], the European LUCAS dataset modeled by [62,63], as well as the U.S. soil spectral data modeled by [23,64,65], were important to show the community the importance and potential of the technique. A free repository such as by [66] have great importance to make this grow since users have access to data. Therefore, our initiative demonstrates the importance of providing online results to end-users and this may encourage other working groups to improve similar new systems.…”
Section: The Web Service Advantages and Limitationsmentioning
confidence: 99%
“…Seidel et al (2019) and Lobsey et al (2017) used the Kennard‐Stone (KS) algorithm to select the given 30 and 20 spiking samples, respectively, from the target site. Summerauer et al (2021) used MBL with 20 spiking samples selected from each of six target sites using the k‐means to predict the soil organic and soil total nitrogen of each site. They gained a noticeable improvement in two sites and gained a slightly improvement in the rest four sites when compared to MBL without spiking samples.…”
Section: Discussionmentioning
confidence: 99%
“…used a given distance calculated from PCA spaces using the Mahalanonis distance to select 30 pairs of most neighbour samples, discarded its neighbours of each pair, and then showed that the optimal spiking number was 10 according to the prediction result Seidel et al (2019). andLobsey et al (2017) used the Kennard-Stone (KS) algorithm to select the given 30 and 20 spiking samples, respectively, from the target site Summerauer et al (2021). used MBL with 20 spiking samples selected from each of six target sites using the kmeans to predict the soil organic and soil total nitrogen of each site.…”
mentioning
confidence: 99%
“…On this foundation, cartographic documentation of soils with a resolution of 30 m was developed and prepared [ 25 ]. The repositories provide 18,250 MIR reflectance recordings [ 26 , 27 ]. A single spectral signature covers 1749 recorded reflectance values in the range from 2500 to 16,666 nm (wavelength 4000 to 600 cm −1 with a step of 1.9 cm −1 ).…”
Section: Methodsmentioning
confidence: 99%